Kirk-Othmer Encyclopedia of Chemical Technology 2000
DOI: 10.1002/0471238961.06150113192108.a01
|View full text |Cite
|
Sign up to set email alerts
|

Foamed Plastics

Abstract: This article is concerned with the general theory of expansion, manufacturing processes, properties, and applications of foamed (cellular) plastics. The high strength‐to‐weight ratio, excellent insulating properties, and cushioning properties of cellular plastics have contributed to the development and growth of the broad range of cellular plastics in use. The total usage of foamed plastics in the United States has risen from 441 thousand metric tons in 1967 to 1.6 million metric tons in 1982 and has been proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…There is a developing literature on the mechanics of foams, see for example Gibson and Ashby [10]. Reviews of earlier work can be found in the articles by Suh and Skochdopole [11] and by Suh and Webb [12], and in the books edited by Wendle [13], Hilyard [14], Hilyard and Cunningham [15] and Banhart [16].…”
Section: Introductionmentioning
confidence: 99%
“…There is a developing literature on the mechanics of foams, see for example Gibson and Ashby [10]. Reviews of earlier work can be found in the articles by Suh and Skochdopole [11] and by Suh and Webb [12], and in the books edited by Wendle [13], Hilyard [14], Hilyard and Cunningham [15] and Banhart [16].…”
Section: Introductionmentioning
confidence: 99%
“…This is also true in the US system, with the introduction of the NGSS. 6 However, the preparation of polyurethane and polystyrene foams in a classroom environment, although not impossible, 7 does offer some practical challenges associated with exposure to toxic reactants, such as isocyanates.…”
Section: Introductionmentioning
confidence: 99%
“…Typical applications of polymeric foams include packaging materials, upholstery, and insulation. Polymeric foams can be prepared from a number of chemistries and methods, but most common types routinely used include polyurethanes and polystyrene . However, the preparation of polyurethane and polystyrene foams in a classroom environment, although not impossible, does offer some practical challenges associated with exposure to toxic reactants, such as isocyanates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymers are foamed by introducing gas bubbles into the liquid monomer or hot polymer, allowing the bubbles to grow and stabilize, and then solidifying the whole thing by cross-linking or cooling [2]. According to Gibson and Ashby [3], there are three sorts of polymer that are used to make foams: thermoplastics, thermosets and elastomers.…”
Section: Introductionmentioning
confidence: 99%